Microorganism-induced weathering of clay minerals in a hydromorphic soil. (1st July 2016) - Hong, Hanlie; Fang, Qian; Cheng, Liuling; Wang, Chaowen; Churchman, Gordon Jock
Abstract: In order to improve the understanding of factors influencing weathering in hydromorphic soils, the clay mineral and chemical compositions, iron (hydr)oxides, organic compounds, and Sr and Nd isotopic compositions, of hydromorphic soils on the banks of the Liangzi Lake, Hubei province, south China, were investigated. The B horizon in the lower profile exhibits a distinct net-like pattern, with abundant short white veins within the red-brown matrix. Their various 87 Sr/ 86 Sr and 143 Nd/ 144 Nd isotopic compositions showed only small variations of 0.7270–0.7235 and 0.51200–0.51204, respectively, consistent with the composition of Yangtze River sediments, indicating that the soils were all derived from alluvium from the catchment. The white veins contained notably more SiO2, Al2 O3, TiO2, and mobile elements relative to the red-brown matrix, while they both showed similar values for the chemical index of alteration of 86.7 and 87.1, respectively, and displayed similar degrees of weathering. The clay minerals in A, AE, and E horizons of the soil profile were illite, kaolinite, and mixed-layer illite–smectite. These same three clay minerals comprised the white net-like veins in the soil B horizon, whereas only illite and kaolinite were observed in the red-brown matrix. Iron (hydr)oxides in A, AE, and E horizons of the soil profile were hematite and goethite, whereas in the red-brown matrix of the B horizon they were hematite, goethite, and ferrihydrite. Different organic compounds were observed for the white vein and the red-brown matrix in the soil B horizon: an 18:2 fatty acid biomarker for fungi in the net-like vein, but not in the red-brown matrix. Compared with the red-brown matrix, the white net-like vein also clearly contained more mono-unsaturated fatty acids, which are sometimes associated with bacteria that have the capacity to reduce Fe(III). Thus, migration of iron and the formation of the net-like veins involved the participation of biota during the hydromorphic pedogenesis process, as ferrihydrite is usually formed with the assistance of biota. Redoximorphic processes will chemically affect phyllosilicates by changing their charge, and Fe(III) in illite may serve as electron acceptor for Fe(III)-reducing microorganisms. This leads to an increase in negative charge in the illite structure which could be neutralized by electrostatic displacement of interlayer cations and adsorption of protons, thereby promoting transformation of illite to mixed-layer illite–smectite and dissolution of the pre-existing illite mineral. Our results suggest that microorganisms brought about iron leaching and dominated the alteration of clay minerals by redox processes, and different mineral volumes formed in the net-like B horizon of the hydromorphic soil were attributed to the microorganism-induced weathering process.